Cultural, morphological and pathogenic variability of Alternaria tenuissima causing blight in pigeonpea of Eastern Uttar Pradesh - R.B. SINGH and S.M. YADAV, LAXMAN PRASAD BALAI*, A. SINHA (Indian Phytopathology, 2016)
Cultural, morphological and pathogenic variabilities of Alternaria tenuissima isolates from pigeonpea were studied. The radial growth of 17 isolates of the pathogen was tested at seven different temperature and PDA medium. The maximum mean radial growth of fungus at temperatures of 25°C and 30°Cwas superior to other temperatures. Whereas, the lowest mean colony diameter was obtained at temperatures of 10°C and 40°C. The radial growth of 17 isolates was superior at 7.0 pH followed by 6.5 pH at five different pH. The least radial growth was obtained at pH of 8.0. Average growth rate after seven days were found varied from 20.0 to 78.0 mm in different isolates. The isolates were categorized in four groups on the basis of variation in radial growth rate. Ten representative isolates from 17 collections were identified and each isolates differed in their conidial size, morphology, length, beak length, width and septal distance. Among the 12 pigeonpea genotypes evaluated against disease, ICP-7220 was found to be highly resistant to alternaria blight followed by IPA-7-2. The most susceptible genotype was MAL-24. Cumulative aggressiveness of different isolates of A. tenuissima also varied significantly on different pigeonpea genotypes. Two Isolates namely At17 and At45 were highly aggressive whereas Isolate At71 was least aggressive on different genotypes of pigeonpea.